Co‑occurring Obsessive‑compulsive Disorder, Autism Spectrum Disorder and Intellectual Disability: A Case Report - Rodrigues, Márcia (2021)
Autism spectrum disorders encompass a wide range of clinical presentations, including obsessive‑compulsive symptoms. The comorbidity between these disorders is significant, and it has therapeutic and prognostic implications. While there are a few references on the approach of such comorbid presentations, the literature is even scarcer when this co‑occurrence is superimposed on individuals with intellectual disability. We present the case of a 43‑years‑old male patient with comorbid treatment refractory obsessive‑compulsive disorder, autism spectrum disorder and intellectual disability, exhibiting subacute symptomatic recurrence including hetero‑aggressive outbursts and contamination obsessions. The phenomenological features and therapeutic strategies are discussed, highlighting the centrality of a patient‑centered and methodologically pluralistic approach. Symptomatic remission was achieved employing high end doses of fluvoxamine and haloperidol, alongside daily psychotherapy involving both symptom‑directed behavioral therapy and supportive psychodynamic techniques. An integrative approach may be the best option in the stabilization of complex cases as the one presented.